Transmission Spectroscopy of Molecular Spin Ensembles in the Dispersive Regime. Issue 9 (1st July 2021) - Bonizzoni, Claudio; Ghirri, Alberto; Nakazawa, Shigeaki; Nishida, Shinsuke; Sato, Kazunobu; Takui, Takeji; Affronte, Marco
Abstract: The readout in the dispersive regime is originally developed—and it is now largely exploited—for non‐demolitive measurement of super‐ and semiconducting qubits. More recently it has been successfully applied to probe collective spin excitations in ferro(i)magnetic bulk samples or collections of paramagnetic spin centers embedded into microwave cavities. The use of this readout technique within a semiclassical limit of excitation is only marginally investigated although it holds for a wide class of problems, including advanced magnetic resonance techniques. In this work, the coupling between a coplanar microwave resonator and diphenyl‐nitroxide organic radical diluted in a fully deuterated benzophenone single crystal is investigated. Two‐tone transmission spectroscopy experiments demonstrate the possibility to reconstruct the spectrum of the spin system with little loss of sensitivity with respect to the resonant regime. Likewise, pulse sequences of detuned microwave frequency allow the measurement of the spin‐lattice relaxation time ( T 1 ). The independent tunability of the probe and the drive power enables one to adjust the signal‐to‐noise ratio of the spectroscopy. These results suggest that electron spin dispersive spectroscopy can be used as a complementary tool of electron spin resonance to investigate the spin response. Abstract : The residual interaction between a planar resonator and a detuned spin ensemble can be exploited to indirectly measure the magnetic signal, through a non‐resonant frequency shift. In this work, this effect is used to perform microwave transmission spectroscopy on a molecular spin ensemble without significant loss of sensitivity with respect to the resonant one.